2019
DOI: 10.1177/1753466619894913
|View full text |Cite
|
Sign up to set email alerts
|

Chronic progressive pulmonary paracoccidioidomycosis in a female immigrant from Venezuela

Abstract: Paracoccidioidomycosis (PCM) is a fungal infection caused by Paracoccidioides brasiliensis and P. lutzii. It is endemic to South and Central America. While PCM frequently remains latent, the disease can reactivate years after the initial infection. As the disease is rare outside the endemic area, and symptoms can mimic other pulmonary diseases, correct diagnosis can be challenging for clinicians in developed countries. In this report, we present the case of a 57-year-old female Venezuelan immigrant with PCM. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Immigrants with chronic disease need more health care and medical treatment provided by primary health services [ 16 ]. However, many studies have shown that immigrants have fewer opportunities to access primary health services, which delays the treatment of chronic diseases and causes anxiety in immigrants [ 17 , 18 ]. It is important and necessary to explore the mental health situation and related factors of immigrants with chronic disease and to provide corresponding primary preventive care policy for immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…Immigrants with chronic disease need more health care and medical treatment provided by primary health services [ 16 ]. However, many studies have shown that immigrants have fewer opportunities to access primary health services, which delays the treatment of chronic diseases and causes anxiety in immigrants [ 17 , 18 ]. It is important and necessary to explore the mental health situation and related factors of immigrants with chronic disease and to provide corresponding primary preventive care policy for immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…However, non-budding or single-budding forms can dominate, which can lead to misdiagnosis [18,19]. Stained with Gomori's methenamine silver, these atypical forms have been confused with other yeast-like pathogens such as Candida, Cryptococcus, or Pneumocystis [18][19][20]. In patients presenting with symptoms concerning an endemic fungal infection and an absence of characteristic pathological morphology, serologic testing can be performed using immunodiffusion and complement-fixing methods to detect antibodies against the fungal pathogen in question [18].…”
Section: Discussionmentioning
confidence: 99%
“…Morphologically, Cryptococcus is a dimorphic fungus that grows in a single-budding yeast form with a distinct polysaccharide capsule [ 17 ]. In contrast, Paracoccidioides takes a spherical, multiple-budding yeast form that resembles that of a ship’s wheel, earning the term “Captain’s Wheel.” However, non-budding or single-budding forms can dominate, which can lead to misdiagnosis [ 18 , 19 ]. Stained with Gomori’s methenamine silver, these atypical forms have been confused with other yeast-like pathogens such as Candida , Cryptococcus , or Pneumocystis [ 18 - 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A detecção de IDD é específica, mas sua sensibilidade varia de 65% a 100%, dependendo da preparação do antígeno utilizado, apesar de ser um método muito utilizado, é necessário a implementação de um teste mais rápido, diante disso os autores avaliaram o ensaio DOT-ELISA, onde se demonstrou ser um meio apropriado para a detecção de anticorpos ou antígenos, no qual os fatos comprovam que além de pontual é muito favorável e versátil, podendo ser usado como de triagem sorológica, pois apresenta uma alta sensibilidade, permitindo que resultados negativos sejam emitidos em um tempo menor que o teste IDD, o que tem grande valor diagnóstico, principalmente por excluir a suspeita clínicas da paracoccidioidomicose. Kayser, et al, (2019) apresentaram um relato clínico onde a paciente emigrante venezuelana foi inicialmente diagnosticada com sarcoidose devido à combinação de sintomas respiratórios e achados radiológicos e histológicos. A diferenciação entre essas doenças pode ser um desafio devido às semelhanças clínicas e histopatológicas (Abreu, et al, 2017).…”
Section: Discussionunclassified